Ecological characteristics of natural and culturated species, their comparison in Prunus genus - Surányi, D. (International Journal of Horticultural Science, 2023)
Plum species are found native throughout the nothern hemisphere, but mostly in the temperate zone. The earliest writings about plum date back some 2000 years (De Candolle, 1894; Cullinan, 1937) puts the age of plums at 2000-4000 years old (Bagenal, 1954). However, the stone core findings suggest a greater past. The question is difficult to conclude because the large number of species of the genus are taxonomically unclear and spread over a wide geographical area. The taxonomic position of stone fruit species and varieties can also be different, especially for Prunus species (Kárpáti, 1967; Terpó, 1974; Raming & Cociu, 1991; Faust & Surányi, 1997; Surányi, 2013). The study analyzes the average relative ecological value measurement numbers of 75 species, including 120 cultivars, in terms of diversity and similarity. It is novel that, based on the sources, the author used the Ellenberg-Borhid values for the European, Asian, North American and other species, expanding them with transitional subgenera (e.g. Microcerasus). It was also possible to pay attention to a North African, Central and South American Prunus/Prunophora species. Following the accounting of economic and fruiting values, the species, subspecies, and varieties of the European and Mediterranean regions are the finalists, but species hybrid plums, rootstocks, or Prunus species whose values have not yet been known can play a role. Although the kéköny is a known species, it can become a cultivated fruit species due to the high antioxidant content of the fruit (Hegedűs & Halász, 2019).